Factors that Influence End-Of-Life Decision Making Amongst Attending Physicians. (October 2022) - Pai, Suraj; Andrews, Tracy; Turner, Amber; Merchant, Aziz; Shapiro, Michael
Background : Medical advances prolong life and treat illness but many patients have chronically debilitating conditions that prevent them from making end-of-life (EOL) decisions for themselves. These situations are difficult to navigate for both patient and physician. This study investigates physicians' feelings and approach toward EOL care, physician-assisted suicide (PAS), and euthanasia.Methods : An anonymous, self-administered online survey was distributed through the New Jersey Medical School servers and American College of Surgeons forums. The survey presented clinical EOL vignettes and subjective questions regarding PAS and euthanasia.Results : We obtained 142 responses from attending physicians. Respondents were typically male (61%), married (85%), identified as Christian (54%), had more than 20 years of experience (55%), and worked at a university hospital (57%). Religious beliefs and years of work experience seemed to be significant contributors in EOL decision making, whereas gender and medical specialty were not significantly influential.Conclusion : Factors such as years of work experience and religious belief may influence medical professionals' opinions about PAS and euthanasia and their subsequent actions regarding EOL care. In many cases, the boundaries are blurred and require further study before concrete conclusions can be made.